Decoding antioxidant and antibacterial potentials of Malaysian green seaweeds: Caulerpa racemosa and Caulerpa lentillifera - Yap, W. F.; Tay, Vangene; Tan, S. H.; Yow, Yoon Yen *; Chew, Jactty * (MDPI, 2019)
Seaweeds are gaining a considerable amount of attention for their antioxidant and antibacterial properties. Caulerpa racemosa and Caulerpa lentillifera, also known as ‘sea grapes’, are green seaweeds commonly found in different parts of the world, but the antioxidant and antibacterial potentials of Malaysian C. racemosa and C. lentillifera have not been thoroughly explored. In this study, crude extracts of the seaweeds were prepared using chloroform, methanol, and water. Total phenolic content (TPC) and total flavonoid content (TFC) were measured, followed by in vitro antioxidant activity determination using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. Antibacterial activities of these extracts were tested against Methicillin-resistant Staphylococcus aureus (MRSA) and neuropathogenic Escherichia coli K1. Liquid chromatography–mass spectrometry (LCMS) analysis was then used to determine the possible compounds present in the extract with the most potent antioxidant and antibacterial activity. Results showed that C. racemosa chloroform extract had the highest TPC (13.41 ± 0.86 mg GAE/g), antioxidant effect (EC50 at 0.65 ± 0.03 mg/mL), and the strongest antibacterial effect (97.7 ± 0.30%) against MRSA. LCMS analysis proposed that the chloroform extracts of C. racemosa are mainly polyunsaturated and monounsaturated fatty acids, terpenes, and alkaloids. In conclusion, C. racemosa can be a great source of novel antioxidant and antibacterial agents, but isolation and purification of the bioactive compounds are needed to study their mechanism of action.